Interdisciplinarity in Teaching Medieval Mysticism: the Case of Angela of Foligno - Mooney, Catherine M. (Horizons, 2007)
This essay addresses two related challenges facing educators who teach about medieval saints, mystics, and their texts. The first is how to relate to the theologies and spiritualities of people who inhabited cultures radically distinct from the modern and postmodern periods. The second regards the contemporary tendency to evaluate medieval believers in terms of modernist intellectual frameworks, most notably clinical psychological categories. A case study approaching the medieval mystic Angela of Foligno from three disciplinary points of view—clinical psychology, historical theology, and cultural history—illustrates how educators might respond to students' penchant to privilege clinical psychology when considering medieval mystics and saints, and shows not only the complementarity of interdisciplinarity, but also its limitations.